Curriculum for integrated learning : a lesson-based approach - Freeland, Kent. (Delmar, 1998)
Themes: making meaning. Time. Diversity. Barbara frietchie. Peter Rabbit. Fingerprints. Boots and shoes. Museum. Shelter. Technology and the curriculum. Art critic. Musically speaking. Movement. Architecture. Food choices. Learning centers, activity cards, and movement.